Elevated cerebral perfusion and preserved cognition in elite Brazilian Jiu‐Jitsu athletes: Evidence for neuroprotection. (13th August 2021) - Stacey, Benjamin S.; Campbell, Zac; Bailey, Damian M.
Abstract: Brazilian Jiu‐Jitsu (BJJ) is a popular martial art that exposes participants to recurrent intermittent asphyxiation due to controlled application of neck chokes. To what extent the sport impacts the regulation of cerebral blood flow (CBF) and cognition has not been examined. This study compared eleven elite Brazilian Jiu‐Jitsu athletes (aged 30 ± 8 y) who trained 12 ± 6 hours/week for 8 ± 4 years against eleven cardiorespiratory fitness (CRF)‐ and age‐matched controls. Internal carotid (ICA) and vertebral artery (VA) blood flow were measured via duplex ultrasound to determine global cerebral blood flow (gCBF). Mild cognitive impairment and sub‐domains of memory, attention/concentration/visual motor coordination, and executive function were determined by psychometric testing. There was no evidence of mild cognitive impairment in the athletes, and cognitive function was comparable between groups (all p  > 0.05). In contrast, resting gCBF was selectively elevated in the athletes (741 ± 186 mL∙min −1 vs. 573 ± 166 mL∙min −1, p  = 0.037) due to combined differences in ICA (+65 mL∙min −1, p  = 0.079) and VA (+19 mL∙min −1, p  = 0.277) flow. In conclusion, the sustained elevation in resting cerebral perfusion provides preliminary evidence for adaptive neuroprotection that is independent of CRF and likely mediated by choke‐induced cerebral preconditioning and/or lifelong exposure to BJJ‐specific high‐intensity interval training.